2019
DOI: 10.1002/leap.1282
|View full text |Cite
|
Sign up to set email alerts
|

The limitations of retraction notices and the heroic acts of authors who correct the scholarly record: An analysis of retractions of papers published from 1975 to 2019

Abstract: While researchers with retracted papers – publications that are withdrawn because of significant errors or scientific misconduct – carry a permanent stain on their publishing records, understanding the causes and initiators of such retractions can shed a different light on the matter. This paper, based on a random sample of 2,046 retracted papers, which were published between 1975 and 2019, extracted from Retraction Watch and the websites of major publishers, shows that 53% of the retraction notices do not spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 50 publications
1
50
1
7
Order By: Relevance
“…The authors thus concluded that retraction notices need to be more informative, and a statement regarding limitations should be required. 17 In our study, we found that although most journals issued a retraction notice, inconsistency and lack of information regarding retracted articles remain prevalent. These studies, in addition to our results, demonstrate that there is still much work to be done to improve transparency and information about retractions for readers of scientific literature.…”
Section: Discussionmentioning
confidence: 71%
“…The authors thus concluded that retraction notices need to be more informative, and a statement regarding limitations should be required. 17 In our study, we found that although most journals issued a retraction notice, inconsistency and lack of information regarding retracted articles remain prevalent. These studies, in addition to our results, demonstrate that there is still much work to be done to improve transparency and information about retractions for readers of scientific literature.…”
Section: Discussionmentioning
confidence: 71%
“…Many databases and search engines, such as Web of Science, Google Scholar and Scopus provide nearly no warning of the retraction in their search results (Teixeira da Silva and Bornemann-Cimenti 2017; van der Vet and Nijveen 2016). In addition, although papers are retracted for different reasons, including selfretraction by the authors and various types of scientific misconduct such as data fabrication, data falsification, unethical author conduct, and plagiarism (Samp et al 2012), about 10% of retraction notices do not indicate the reason for the retraction (Bozzo et al 2017;Moylan and Kowalczuk 2016;Vuong 2020), making it difficult for a reader to determine the scope or severity of the problem (Guengerich 2015;Marcus and Oransky 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To improve dissemination and reporting of the scholarly record, some have argued that journals should make authors' study limitations public and freely available [5]. Typically, limitations are detailed in the Discussion section [6], although occasionally they may also appear in the Abstract [3].…”
Section: Introductionmentioning
confidence: 99%